The Effect of Service Quality on Individual Credit Customer Satisfaction (Case Study at BMT UGT Sidogiri Lumajang Branch) - Abdul Rahim (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This research was conducted using five variables that are thought to influence customer service satisfaction. The five independent variables are: reliability , responsiveness , empathy , assurance , tangible . The research objective to be achieved is to examine the influence of the five independent variables on customer satisfaction, either partially or simultaneously. In this study, the population includes all BMT UGT Sidogiri customers, Lumajang Branch, r. The technique used in determining the sample is random sampling technique . Data collection methods that will be used in this study are interviews, questionnaires and documentation. This research is a quantitative research with data analysis methods using the Multiple Linear Regression statistical analysis method with the formula . Based on the results of the multiple linear regression analysis, it can be seen that the contribution or influence of the independent variables consists of reliability (X1 ), responsiveness (X2 ), empathy (X3 ), assurance (X4 ) and tangible (X5 ) on customer satisfaction of BMT UGT Sidogiri Lumajang is as big. 99.9% while the remaining 0.01%. influenced by other factors outside the model The P value for the reliability variable (X1 ) = 0.000 which means it is significant at α = 0.05 then H 0 is rejected which means β i ≠ 0. So it can be concluded that the reliability variable (X1 ) has a significant effect individually on BMT UGT Sidogiri Lumajang customer satisfaction. The P value for the responsiveness variable (X 2 ) = 0.009 which means it is significant at α = 0.05 then H 0 is rejected which means β i ≠ 0. So it can be concluded that the responsiveness variable (X2 ) individually significant effect on customer satisfaction BMT UGT Sidogiri Lumajang. The P value for the empathy variable ( X3 ) = 0.000 which means it is significant at α = 0.05 then H 0 is rejected which means β i ≠ 0. So it can be concluded that the empathy variable (X3 ) has a significant effect individually on BMT UGT Sidogiri Lumajang customer satisfaction. The P value for the assurance variable ( X4 ) = 0.469 which means it is not significant at α = 0.05 then H 0 is accepted which means bi = 0. So it can be concluded that the assurance variable (X4 ) has no effect individually significant to BMT UGT Sidogiri Lumajang customer satisfaction. The P value for the tangible variable (X5 ) = 0.000 which means it is significant at α = 0.05 then H 0 is rejected which means β i ≠ 0. So it can be concluded that the tangible variable (X5 ) has a significant effect individually on BMT UGT Sidogiri Lumajang customer satisfaction. The variable that has the most dominant influence on customer satisfaction at BMT UGT Sidogiri Lumajang Branch is the variable reliability (X1 ).